Factors Affecting Low Back Pain among ICU Nurses - Dadang Rochman; Henny Suzana Mediani; Aan Nur’aeni (Faculty of Nursing Universitas Padjadjaran, 2018)
Low back pain is a pain syndrome that is often felt in the lower back region accompanied by spreading to the legs. It is often associated with work-related musculoskeletal disorders. This condition is often experienced by the Intensive Care Unit (ICU) nurses, from mild to severe LBP, which may affect the productivity of work and physic of the nurses. Aim to analyze and explore the factors that affected the number of low back pain incidents in ICU nurses in hospitals in the Banten Province. This study used the correlational analytic method with a crosssectional approach. The study sample was 82 ICU nurses, obtained by total sampling. Data collection used the LKQ questionnaire (Low back pain Knowledge Questions) and observation sheets. Data analysis used the Chisquare and multiple logistic regression analysis with a prediction model. Knowledge factor p (0.001), height p (0.021), night shift frequency p (0.003), and weight with a p-value (0.021) had a significant relationship with low back pain, whereas the ICU space environment factor p (0.668), work period p (0.462), and age p (0.079) did not have a significant relationship with low back pain. From related factors, knowledge had the most significant relationship with low back pain incident (OR = 38.62). This study has significantly proven that knowledge, height, weight, and frequency of night shifts affected the low back pain in ICU nurses. The nurse’s knowledge factor is the most influential factor of low back pain incident in ICU nurses. Increasing the ICU nurse’s knowledge about body biomechanics by following training and developing standard operating procedures. It is suggested to reduce the amount of excessive night shift burden ICU nurses, select and setting criteria for nurses working in the ICU.